PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL MUATAN PEMBELAJARAN IPA MATERI SIFAT-SIFAT CAHAYA PADA SISWA KELAS IV SDN JATISARI KECAMATAN SLUKE KABUPATEN REMBANG TAHUN PELAJARAN 2018/2019 - Masmulyono Masmulyono (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2022)
This study aims to determine the learning outcomes of plant structure material in fourth grade students of SDN Jatisari through the use of project based learning models. This type of research is classroom action research (CAR). The research subjects were 30 students. Data collection techniques by observation, interviews, and documentation. The data analysis used is descriptive qualitative data analysis. The results showed that the mastery of the first cycle with the classical percentage of 53% (medium) and the second cycle with the classical percentage of 87% (very good). Affective domain learning outcomes increased from 66.75% (good), in the second cycle the percentage was 78% (good). Psychomotor learning outcomes increased from a percentage of 65.65% (good), while in the second cycle the percentage was 78.05% (good). From the explanation above, it can be concluded that the application of the Project Based Learning model can improve learning outcomes for fourth grade students at SDN Jatisari in the science learning content of the material properties of light.